AME+Cyber: Evaluating the online delivery of a holistic cyber-related talent development program. (January 2022) - Desmet, Ophelie; Crimmins, Danielle; Seigfried-Spellar, Kathryn C.; Gentry, Marcia
The present study used an explanatory mixed-method design to examine the effects of the Achievement Motivation Enhancement (AME)+Cyber enrichment program and teachers' perception of procedures and outcomes in the context of emergency remote teaching, including online and hybrid formats, during the COVID-19 pandemic. Three teachers implemented the program with 57 students in grades 9 through 12. To evaluate the program, we combined change score analysis of pretest and posttest data on academic self-perception, self-regulation, goal valuation, cyber-related interest, as well as descriptive interpretative analysis of interview data. We found the online learning format was more effective than the hybrid format for the affective and cognitive outcomes. Qualitative findings suggested pedagogical concerns and struggle with online learning due to emergency remote teaching during the COVID-19 pandemic, centered around a lack of student engagement and interaction that appropriate levels of training and practice could remedy. Implications and future research suggestions are discussed.